Weldability of metal matrix composite plates by friction stir welding at low welding parameters - (:unkn) unknown (My University, 2011)
Metal matrix composites (MMCs) are engineering materials that their increasingly replacing of a number of conventional materials in automotive, aerospace, and sports industries is driven by the demand for lightweight, high specific strength and stiffness. Their wide application as structural materials needs proper development of suited joining processes. Friction stir welding (FSW) is a fairly new solid state welding process for joining metals using thermal energy produced from localized friction forces. In this study, the weldability of AA2124 containing (volume fractions) 25 % of SiC particles with T4 heat treated aluminum MMC plates was investigated at low welding parameters by FSW process. Microstructure, ultimate tensile strength, surface roughness and microhardness determination have been carried out to evaluate the weld zone characteristics of friction stir welded MMC plates. The FSW specimens were tested without post-weld heat treatment or surface modification. The temperature dissipation at the distance of 15 mm from the weld center was also measured using K-type thermocouples to demonstrate the FSWed joining without melting. Because of microstructural modification, improvement of microhardness of the stir zone was observed in comparison to the base composite. Ultimate tensile tests indicated a joint efficiency of approximately 73 %.
Keywords: Friction stir welding; Metal matrix composites; Microstructure; Welding parameters